Gioia Angeletti, Nation, Community, Self: Female Voices in Scottish Theatre from the late Sixties to the Present (Altre Modernità, 2022)
Gioia Angeletti, Nation, Community, Self: Female Voices in Scottish Theatre from the late Sixties to the Present (Milano, Mimesis International, 2018, 250 pp. ISBN 978-886-977-134-7) by Anna Caterino